The Educational Impact of a Fellowship-trained Orthopaedic Oncologist. (July 2020) - Wells, Matthew E.; Eckhoff, Michael D.; Schneider, Phillip R.; Kafchinski, Lisa A.; Dunn, John C.; Gonzalez, Gilberto A.
Abstract : Introduction: Musculoskeletal oncology is a subspecialty of orthopaedics with few fellowship-training locations. Although orthopaedic oncologists comprise a minority within the field of orthopaedic surgery, most work at academic centers and serve in leadership roles with notable impact on patients and the training of residents. This article investigates the objective impact orthopaedic oncologists have regarding resident operative case volume and performance on in-training examinations. Methods: The William Beaumont Army Medical Center and Texas Tech University Health Sciences Center of El Paso combined orthopaedic residency program's case logs and Orthopaedic In-Training Examination (OITE) scores between 2013 and 2018 were reviewed. This provided 3 academic years of data before and after an orthopaedic oncology faculty member arrived in 2016. The case volume and OITE examination performance before and after the addition of the orthopaedic oncology faculty member were compared. Results: After the addition of an orthopaedic oncology faculty member, a significant increase was observed in the program's OITE overall correctly answered questions (171.30 versus 181.03, P = 0.004) and oncology subsection percentile (56th to the 66th percentile, P = 0.038). An increase was also observed in resident oncology case volume from 29 oncology cases per year to 138 cases on average ( P = 0.022). Discussion: The addition of a fellowship-trained orthopaedic oncologist results in increased exposure to orthopaedic oncology cases and improved resident performance on the OITE. This may correlate to improved American Board of Orthopaedic Surgeons Part I pass rates and improved overall resident satisfaction.